Laboratory and field-based assessment of maximal aerobic and anaerobic power in professional tennis players - Kilit, B.; Arslan, E. (International Journal of Sports Science, 2016)
The purposes of this study were to determine the relationship between laboratory and field aerobic and anaerobic tests performances in professional tennis players. Fourteen professional tennis players (age 23.0 ± 1.9 years; height 178.9 ± 3.5 cm; weight 73.9 ± 7.6 kg; training experience 7.1 ± 1.1 years) participated in this study voluntarily. A portable gas-analysis system was used during the laboratory treadmill running testing (TRT). Field-based assessments were performed using the Hit and Turn Tennis Test (HTTT), the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT) and the 20-m Multistage Shuttle Run Test (MSRT). The Wingate anaerobic test (WAnT), jumping ability (counter-movement jump (CMJ) and squat jump (SJ), and sprinting ability (5-m, 10-m and 20-m) were used for the determination of anaerobic performances. The results demonstrated that the distance covered in TRT was significantly correlated with all field tests in terms of distance covered (ranging from r = 0.56-0.64; p < 0.05). Significant correlations were also found between HTTT and TRT in terms of VO2max response (r = 0.46; p < 0.05). Moreover, the maximal running velocity calculated from the field tests was significantly correlated with the WaNT, jumping and sprinting abilities (ranging from r = 0.40-0.81; p < 0.05). The results of this study suggest that HTTT may be more suitable sport specific field test for determining required aerobic capacity responses in tennis players.